Geopolitical risk and environmental degradation in BRICS: Aggregation bias and policy inference. (July 2022) - Riti, Joshua Sunday; Shu, Yang; Riti, Miriam-Kamah J.
Abstract: Currently, the high incidence of environmental degradation is widely quoted as one of the key global concerns. Previous literature has examined various determinants of environmental degradation, yet, there is an inadequacy of studies on geopolitical risks (GPR) and environmental degradation nexus. Additionally, an issue of concern on aggregate estimations is aggregation bias which may cause the wrong estimation of the aggregate relationships, and mislead policymakers. This paper, therefore, investigates the impact of GPR on the environment of BRICS to assess the existence or otherwise of aggregation bias. The findings which emanate from a robust empirical estimation indicate that the relationship is positive at aggregate level while negative at disaggregated level, hence, the existence of aggregation bias in the estimation of GPR-environmental degradation relationship at the aggregate level. The results further show that the disaggregated level result does not support the aggregated level environment-GPR findings. Consequently, policy implications of aggregation bias in estimations may be drawn as follows: Since the aggregation bias may lead to a wrong environment-GPR postulation, policymakers could be misinformed by the incorrect evidence to give wrong policies about environmental concerns. Also, policymakers should consider the environment-GPR nexus at both aggregate and country-specific levels when making environmental policies. Highlights: The impact of geopolitical risks (GPR) on environmental degradation of BRICS is examined. The issue of aggregation bias in aggregate relationships is also investigated. The relationship is positive at aggregate level while negative at disaggregated level, hence, aggregation bias exists. Results indicate that aggregate level environmental policies can still have individual impacts on each country. Policies can be given at both the aggregate or panel level and at country or cross section-specific level.